Iatrogenic esophageal perforation that could be treated indirectly by cervical esophagostomy and laparoscopic surgery. (2019) - Matsui, Ryohei; Takayama, Satoru; Hattori, Taku; Imagami, Toru; Sakamoto, Masaki; Kani, Hisanori
Highlights: It is very rare case that each esophageal stump become connected and patent spontaneously. Two-stage surgery is useful for esophageal perforation if radical operation is difficult. Esophageal perforation can be resolved without direct closure if appropriate drainage is performed. Abstract: Introduction: Successful nonoperative management has been reported for esophageal perforation; however, some cases require surgery. Case presentation: We presented the case of an 85-year-old woman with iatrogenic thoracic esophageal perforation in whom primary repair or resection of the perforated esophagus was difficult because she was elderly and had severe aortic valve stenosis. Therefore, we selected a two-stage surgery; laparoscopic gastrostomy, jejunostomy, posterior mediastinal drainage, and cervical esophagostomy were performed. We planned reconstruction after the perforation was closed, but endoscopic examination revealed spontaneous patency of each esophageal stump. Endoscopic balloon dilation was necessary because of esophageal stenosis; however, anastomotic surgery was unnecessary. Conclusion: This case report suggests that esophageal perforation is resolved without direct closure if appropriate drainage is performed.